Comprehensive Analysis of Fuel Cell Electric Vehicles: Challenges, Powertrain Configurations, and Energy Management Systems - Md Shahin Munsi; Ravi P. Joshi (IEEE Access)
Rising concerns about fuel costs, emissions, oil depletion, and energy security have propelled the search for alternative energy sources in transportation. Electric vehicles are a crucial development in this direction, and fuel cell technology is gaining traction for its versatility and potential benefits. Fuel cells have become increasingly attractive for automobile owing to their ease of use, quiet operation, superior efficiency, modular design, and reliance on clean hydrogen. However, challenges remain, including hydrogen storage, high costs, integration with power electronics, and cold-start capabilities, which continue to impede the widespread adoption of Fuel Cell Electric Vehicles (FCEVs). This study critically examines these key issues, explores various fuel cell technologies and drivetrain architectures, and provides a comparative analysis of different energy storage systems. Furthermore, the study delves into the classification and evaluation of energy management strategies (EMS) for FCEVs. The review ultimately aims to stimulate further research focused on reducing costs, extending fuel cell lifespan, enhancing hydrogen infrastructure, optimizing electronic interfaces, and refining EMS to pave the way for the future of FCEVs.